Valine potentiates cefoperazone-sulbactam to kill methicillin-resistant Staphylococcus aureus - Shao-hua Li; Yuan Tao; Zhi-cheng Yang; Huan-zhe Fu; Hui-yin Lin; Xuan-xian Peng; Hui Li (mSystems)
ABSTRACT Metabolic state-reprogramming approach was extended from Gram-negative bacteria to Gram-positive bacterium methicillin-resistant Staphylococcus aureus (MRSA) for identifying desired reprogramming metabolites to synergize existing antibiotic killing to MRSA. Metabolomics comparison between MRSA and methicillin-sensitive Staphylococcus aureus showed a depressed metabolic state in MRSA. Valine was identified as the most depressed metabolite/biomarker, and valine, leucine and isoleucine biosynthesis as the most enriched metabolic pathway. Thus, valine was used as a reprogramming metabolite to potentiate existing antibiotic killing to MRSA. Among the tested antibiotics, valine synergized cefoperazone-sulbactam (SCF) to produce the greatest killing effect. The combined effect of SCF and valine was demonstrated in clinical MRSA isolates and in mouse systemic and thigh infection models. Underlying mechanisms were attributed to valine-induced the activation of the pyruvate cycle/the TCA cycle and fatty acid biosynthesis. The activated pyruvate cycle/the TCA cycle elevated proton motive force by NADH and the activated fatty acid biosynthesis promoted membrane permeability by lauric acid. Both together increased cefoperazone uptake, which outpaces efflux action and thereby intracellular drug is elevated to effectively kill MRSA. These results provide the combination of valine and SCF to produce a new drug candidate effective against MRSA.IMPORTANCEMethicillin-resistant Staphylococcus aureus (MRSA) is possibly the most infamous example of antibiotic resistance and new antibiotics are urgently needed to control it. The present study used metabolic state-reprogramming approach to identify an ideal biomarker as an antibiotic adjuvant for reversing the metabolic state of MRSA. The most repressed valine was identified as the adjuvant. Exogenous valine most effectively potentiated cefoperazone-sulbactam (SCF) to kill MRSA in vitro and in vivo. Viability of 18 clinical MRSA isolates was reduced by the top 276.64-fold in the presence of valine and SCF. In mouse models, lower bacterial load in liver, spleen, kidney, thigh, and higher survival were determined in the SCF + valine than valine or SCF alone. Valine promoted MRSA to increase SCF uptake that overcomes the efflux and enzymatic hydrolysis. It also extended the PAE of SCF. These occur because valine activates the pyruvate cycle to elevate proton motive force by NADH and increases membrane permeability by lauric acid. Therefore, the combination of valine and SCF is a new drug candidate effective against MRSA.